Community Ecology of Understorey Tropical Rainforest Birds in Western Sarawak - Hanis Damia Elyna, Lit (Universiti Malaysia Sarawak (UNIMAS), 2021)
Habitat changes have influenced the community structure of understorey birds and their sensitivity towards habitat alteration and landscape modification may influence habitat selection and foraging efficiency. This study mainly focused on understorey bird community structural assemblages as a function of habitat preference and the predictive factors that influence their spatial distribution. The objectives of this study is (1) to determine the species diversity, species richness and abundance of understorey birds, (2) to determine the composition of insect in the diet birds and to relate the abundance of insect to breeding and moulting patterns of insectivorous and frugivorous-insectivorous, (3) to investigate habitat characterictics that influence understorey birds assemblages, and (4) to elucidate the morphological variation of families Timaliidae, Pycnonotidae, Nectariniidae, and Muscicapidae. The community ecology of understorey tropical rainforest birds at eight sites in western Sarawak was investigated between March 2015 and April 2017 by using a total of 20 mist-nets with three shelves (2.5 m x 9 m, 36 mm mesh) at every occasion and were deployed at 20 of 20 x 20 m plots in census site. A total of 1779 individuals representing 131 species from 35 families were recorded across all study sites. Findings generated from Principal Component Analysis and Generalized Linear Model indicated that high species richness and diversity in mixed dipterocarp, mangrove and kerangas forests are determined by canopy cover, density of flowering plant and density of woody plant with more than 3 m height respectively. Thus, this thesis makes an important contribution to our understanding of relative effects of habitat characterictics in bird assemblages at multiple spatial scales and provides important ecological information for the management authority of protected areas.